Somatic MED12 Nonsense Mutation Escapes mRNA Decay and Reveals a Motif Required for Nuclear Entry. Issue 3 (11th January 2017) - Heikkinen, Tuomas; Kämpjärvi, Kati; Keskitalo, Salla; von Nandelstadh, Pernilla; Liu, Xiaonan; Rantanen, Ville; Pitkänen, Esa; Kinnunen, Matias; Kuusanmäki, Heikki; Kontro, Mika; Turunen, Mikko; Mäkinen, Netta; et al.
Abstract : We analyzed the functions of a MED12 5′ end nonsense mutation (c.97G>T, p.E33X) identified in acute lymphoblastic leukemia and showed that the mutation escapes nonsense mediated mRNA decay (NMD) by using an alternative translation initiation site. The inability of the N‐terminally truncated mutant protein to enter the nucleus abolished all interactions between MED12 and the Mediator complex components and led to the identification of a nuclear localization signal (NLS) in the MED12 protein. ABSTRACT: MED12 is a key component of the transcription‐regulating Mediator complex. Specific missense and in‐frame insertion/deletion mutations in exons 1 and 2 have been identified in uterine leiomyomas, breast tumors, and chronic lymphocytic leukemia. Here, we characterize the first MED12 5′ end nonsense mutation (c.97G>T, p.E33X) identified in acute lymphoblastic leukemia and show that it escapes nonsense‐mediated mRNA decay (NMD) by using an alternative translation initiation site. The resulting N‐terminally truncated protein is unable to enter the nucleus due to the lack of identified nuclear localization signal (NLS). The absence of NLS prevents the mutant MED12 protein to be recognized by importin‐α and subsequent loading into the nuclear pore complex. Due to this mislocalization, all interactions between the MED12 mutant and other Mediator components are lost. Our findings provide new mechanistic insights into the MED12 functions and indicate that somatic nonsense mutations in early exons may avoid NMD.